2017
DOI: 10.1200/jop.2016.019729
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Satisfaction and Adherence to Oral Chemotherapy in Patients With Cancer

Abstract: Women and patients who reported increased treatment satisfaction and reduced burden to others were more adherent to oral chemotherapy. Interventions that help patients improve communication with clinicians and reduce burden may optimize oral chemotherapy adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 59 publications
3
88
2
3
Order By: Relevance
“…In addition, those with greater cancer-related symptom severity and interference, worse fatigue, lower satisfaction with treatment and communication with clinicians, higher anxiety and depressive symptoms, and lower perceived social support had worse QoL. Contrary to previous literature showing a positive association between QoL and adherence to cancer therapies, 14,16 these constructs were not related in our sample. Higher anxiety was most strongly related with worse QoL, with even minimal increases in anxiety associated with large and clinically meaningful reductions in QoL.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…In addition, those with greater cancer-related symptom severity and interference, worse fatigue, lower satisfaction with treatment and communication with clinicians, higher anxiety and depressive symptoms, and lower perceived social support had worse QoL. Contrary to previous literature showing a positive association between QoL and adherence to cancer therapies, 14,16 these constructs were not related in our sample. Higher anxiety was most strongly related with worse QoL, with even minimal increases in anxiety associated with large and clinically meaningful reductions in QoL.…”
Section: Discussioncontrasting
confidence: 96%
“…Patients with greater symptom distress and interference also tended to have poorer adherence, consistent with recent findings of a study on adherence and symptom distress, 13 and our previous study showing that patients with cancer who reported higher symptom distress over time experienced poorer medication adherence. 16 As the number of patients receiving oral cancer therapies continues to increase, the process for monitoring side effects and managing adherence requires attention. Although patients report preference for oral administration, 3 few studies have compared QoL in patients prescribed oral versus intravenous chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that women are more adherent than men. 39 We did not find a gender difference in adherence to capecitabine. Also, we did not find any association between adherence and self-efficacy for chronic disease management.…”
Section: Effectiveness Of Self-managementmentioning
confidence: 49%
“…In addition, a literature review suggests that greater treatment satisfaction is associated with better treatment compliance and improved persistence . Patients with RRMM require long‐term treatment, and those who are satisfied with their treatments are more likely to participate in the management of their disease, adhere to therapy, and achieve the best possible outcomes . Whether convenience impacts adherence in MM needs to be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 99%